Desarrollo de un recurso didáctico basado en realidad aumentada sobre las especies endémicas del jardín botánico Reinaldo Espinosa, como apoyo al proceso de enseñanza-aprendizaje en la asignatura de ciencias naturales, para los estudiantes de décimo año de educación general básica de la escuela José Ingenieros Nº 1 de la ciudad de Loja, período 2015 - Jaramillo Quito, Tatiana Fernanda (2016)
This research work entitled "Development of a teaching resource based on augmented reality on endemic species of the Botanical Garden Reinaldo Espinosa, to support the teaching-learning process in the subject of Natural Sciences, for students in the tenth year of general basic education School "José Ingenieros" No. 1 of the city of Loja, period 2015. "part of the problem manifested in the students' lack of interest in the matter, and the need to implement new information technology and Communication as a tool for teaching support and making progress in education. Therefore due to this problem an educational resource based on augmented reality as an interactive tool which allows you to combine the real world with the virtual achieving and display images and videos third dimension through mobile devices was developed. For the development of research the scientific method was used because it is organized in phases allowing for the orderly investigation, on the other hand to achieve the end product of a teaching resource waterfall methodology covers the necessary steps for its implementation was used ; He began by obtaining the requirements by the survey of two teachers and 32 students, we proceeded to perform the design phase in which the teaching resource model to develop later described; in the testing phase we proceeded to conduct socialization where indicated as make use of this tool, as well as selected issues ultimately sheet valuation in which technical, educational, functional aspects are considered applied and quality the material, in order to ensure the functioning and teaching effectiveness. It is noteworthy that the teaching resource is easy to use, interactive, dynamic, motivating and helps facilitate the process of learning of the subject of Natural Sciences.